If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7+x=-3(1+x)
We move all terms to the left:
-7+x-(-3(1+x))=0
We add all the numbers together, and all the variables
x-(-3(x+1))-7=0
We calculate terms in parentheses: -(-3(x+1)), so:We get rid of parentheses
-3(x+1)
We multiply parentheses
-3x-3
Back to the equation:
-(-3x-3)
x+3x+3-7=0
We add all the numbers together, and all the variables
4x-4=0
We move all terms containing x to the left, all other terms to the right
4x=4
x=4/4
x=1
| 8r+10+7r=10r-10 | | 3000=1.05^x | | 100+80x+88+92=360 | | -4u-3=-9-5u | | -5+g=-5+3g | | 12v=9-v | | 9s-4=10 | | 5/8-5/8s=2-s | | 1.3(d-5)=-1.3 | | x³-x²+x=10 | | 20.80=0.4x | | 4-3/5m=6-5m+2 | | (3x-2)/4+(10x-8)/12=13/4+(x-2)/3 | | 8-8s=10s-10 | | -20-11n=9 | | 7.9-2q=11.9 | | 6x+54x+1=2 | | 7.9-2q=-11.9 | | -5r-2=23 | | 1/2v+8=3-1/3v | | -0.53=h+7.31/2 | | -p+2=7p-6 | | -18=-2-8/3w | | -9v+6=8v | | -2/9u-18=-6 | | -2/9u-18=6 | | Nx2=7+9 | | 4.29+4s=19.89 | | -2x+(-3x)+1=-x+11+(-2x) | | -2u+1(1-)=-13 | | -5j-4=5j+6 | | 3y+68=-14y |